Ensino e aprendizagem de Biologia em trilhas interpretativas: o modelo contextual do aprendizado como referencial - Araujo, Elaine Sandra Nicolini Nabuco de [UNESP]; Soman, José Marcelo [UNESP]; Caluzi, João José [UNESP]; Caldeira, Ana Maria de Andrade [UNESP] (My University, 2011)
The current study had as its aim to investigate the factors which have influenced the Biology learning in interpretative trial, through of contextual model of learning, proposed by John Howard Falk for research at museums and science centers. Participated of this study, students from the seventh level that realized guided visits at environmental preservation area, located at Botucatu - SP. From the obtained results in such study, we have identified the similarities and differences among the factors which bias the learning process at museums and natural ambient. For school visits to the natural ambient, we identified several elements of personal contexts, sociocultural and physical and that the factor choice and control (personal context) operates on a limited basis. Due to importance of this factor in learning, we believe that there is need for further investigations, based on the interests of students, to enable the development of specific activities for outdoor museums.

O presente estudo teve por objetivo compreender os fatores que influenciam na aprendizagem de Biologia em trilhas interpretativas, a partir do modelo contextual do aprendizado proposto por John Howard Falk para estudos em centros e museus de Ciências. Participaram de nossa investigação, cinco turmas de alunos do 7º ano que realizaram visitas monitoradas a uma área de preservação ambiental, localizada no município de Botucatu-SP. A partir dos resultados obtidos, constatamos semelhanças e diferenças entre os fatores que influenciam na aprendizagem em museus indoor e em ambientes naturais. Em relação a visitas escolares a esses últimos, identificamos diversos elementos dos contextos pessoal, sociocultural e físico e uma operacionalização limitada do fator escolha e controle (contexto pessoal). Tendo em vista a importância desse fator para aprendizagem, entendemos que há necessidade de novas investigações, baseadas nos interesses dos alunos, que possibilitem o desenvolvimento de atividades específicas para museus outdoor.
Teaching and learning Biology on interpretative trails: the contextual model of learning as referential
Keywords: Contextual model of learning; Natural environment; Teaching biology; Modelo contextual do aprendizado; Ambiente natural; Ensino de Biologia